2021
DOI: 10.1007/s12204-021-2304-6
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Application of 3D Printing Technology in Spine Surgery

Abstract: We are in the midst of exciting advancements in new technologies and innovative research in precision medicine. Among these, 3D printing is one of the most frequently seen in clinical orthopaedic settings. This new technique has been adopted in a vast range of applications in spine surgery, such as producing anatomical models, surgical templates, preoperative plans, and spinal implants. Some studies on 3D printing technologies in spine surgery have reported the benefits of this emerging technology with more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…3D printing technology has been found to have considerable application value in the medical field (Mayfield et al, 2022;Moralidou et al, 2022), particularly in Spine Surgery (Sun et al, 2021;Fan et al, 2022). Through 3D printing technology, the operator's ideas can be incorporated into the 3D printed products.…”
Section: Discussionmentioning
confidence: 99%
“…3D printing technology has been found to have considerable application value in the medical field (Mayfield et al, 2022;Moralidou et al, 2022), particularly in Spine Surgery (Sun et al, 2021;Fan et al, 2022). Through 3D printing technology, the operator's ideas can be incorporated into the 3D printed products.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned 21 , spinal osteotomy is still a risky technique that can lead to injuries and requires previous training. Therefore, AMSCSA of TPS and LPS are innovatively useful tools to expose students to the most common surgical techniques for spinal cord decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Patton et al [ 11 ] found that catastrophic screw placement occurred in 33.3% of the patients with fluoroscopy-guided free-hand screw placement, compared with a significantly lower but still high incidence of 16.7% in the image-guided group. It is shown that patient-specific drill templates (PDTs) made by three-dimensional printing technology (3DP) had favorable effectiveness and accuracy in assisting cervical transpedicular screw placement [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%